Let Young People Join The Legislative Process. A Twitter Based Experiment On Internships - Paolo Nicola Barbieri; Francesca Fazio; Gabriele Gamberini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
The aim of this research is to examine the possible effects of labour market institutional characteristics on young people's perceptions of their internship experiences as expressed on Twitter. By looking at these opinions (satisfaction versus dissatisfaction) in relation to certain features of internships as well as to the more general labour market regulatory framework, this project aims to give a voice to young people, enabling them (indirectly) to provide policy suggestions to law-makers. Furthermore, we propose a preview of a possible empirical model for data collection based on the manual coding of Tweets. By employing a Probit regression and Blinder-Oaxaca and Fairlie decompositions, we have tried to establish a link between the perceived evaluation of internships and the country where the internship is based, the latter being used as a proxy for the legal system. In all our tests we found that the country in which the internship is placed is the main factor in the positive or negative perception. Ultimately we shall propose the use of Twitter not only as a relevant research tool, but also as an instrument for bringing young people's needs to the attention of law-makers.
Keywords: J28; K31; Z13; 330